Making `us` better: High-quality athlete leadership relates to health and burnout in professional Australian football teams - Fransen, K.; Haslam, S. A.; Steffens, N. K.; Mallett, C. J.; Peters, K.; Boen, F. (European Journal of Sport Science, 2020)
Overtraining, exhaustion, and burnout are widely recognized problems amongst elite athletes. The present research addresses this issue by exploring the extent to which high-quality athlete leadership is associated with elite athletes` health and burnout. Participants (120 male athletes from three top-division Australian football teams) were asked to rate the quality of each of their teammates in four different leadership roles (i.e. as task and motivational leaders on the field and as social and external leaders off the field), and also to indicate their identification with their team as well as their self-reported health and burnout. Findings indicated that (a) being seen to be a good athlete leader by other members of the team and (b) having a good athlete leader on the team were both positively associated with better team member health and lower burnout. This relationship was mediated by athletes` identification with their team, suggesting that leaders enhance athletes` health and reduce athlete burnout by creating and maintaining a sense of shared identity in their team. This, in turn, suggests that coaches can foster an optimal team environment by developing the leadership potential of their athlete leaders - in particular, their skills that foster a sense of shared team identification. This is in the interests not only of team performance but also of team members` health and burnout. Keywords: Shared leadership, peer leadership, team identification, social identity approach